Pengaruh Model Discovery Learning Berbantuan Media Audiovisual terhadap Keterampilan Menulis Teks Berita Siswa Kelas VII SMPN 1 Lubuk Basung - Belinda, Bunga Mutiara; R, Syahrul (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2024)
This research is motivated by the low news text writing skills of grade VII students of SMPN 1 Lubuk Basung, which is caused by low interest in learning, poor understanding of the material, and lack of motivation and variation in learning models. Therefore, a more effective learning approach is needed to improve student learning outcomes in writing news texts. This study aims to describe students' news text writing skills before and after using the discovery learning model assisted by audiovisual media, and to measure the effect of the model on students' writing skills. The method used in this study is an experimental method with a quantitative design. Data were analyzed using percentage formulas, arithmetic averages, data analysis requirements tests, and t-tests. The results showed that the application of the discovery learning model assisted by audiovisual media had a positive impact on students' news text writing skills. This study concludes that the use of appropriate learning models and media can significantly improve students' writing skills, as well as encourage their creativity and interest in learning.